Migration management – the cases of Germany and Hungary - Milosavljević, Zoran; Maksimović, Andrijana R. (Serbian Journal of Management, 2023)
The authors of the paper deal with immigration policies, migration management, migration management policy via case study based on the example of two purposefully chosen countries which have diametrically opposite immigration policies. The aim is to see up to which extent and whether these countries are interested into integrating immigrants into their social, legal, political and cultural space, through their institutional capacities, by the means of comparative analysis of German and Hungarian immigration policies, their social, demographic and economic structure, and their cultural and security policies. By defining concepts of migration, immigration, integration, immigration policy, migration management, immigration border management, the authors precisely pinpoint the differences, and the causes of those differences, in the policies towards migrants in these two countries.
Keywords: migration management; case study; Germany; Hungary; integration; immigrant policy